Bahasa Inggris - Rahman, Nurain; Agusrianto Yusuf; Mindy Eka Astuti (Journal of Health, Technology and Science (JHTS), 2023)
The purpose of this study was to compare the results of the examination and determine the factors that affect blood glucose levels while with fasting blood glucose levels in patients with diabetes mellitus at Toto Kabila Hospital.This research method uses a quantitative research approach with the type of research used in this study is an analytical observational research type. The population in this study were all patients with diabetes mellitus who had an examination. The sample used was 30 patients with a sampling technique using purposive sampling.The results of this study indicate that the factors that affect blood glucose levels during and fasting are age, obesity, genetic history and lifestyle, and there are differences in the results of the examination. fasting blood glucose and fasting blood glucose where the results of non-parametric analysis with a significant value (2-Tailed) that is .000 <0.05, from the results obtained the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.